(untitled) (Advancements in Homeopathic Research, 2022)
Studying adenocarcinoma cells and the new therapies to treat cancer is a promising area of interest. Adenocarcinoma in breast can be of several types, and different cell lines are in use because they have several characteristics similar to those of mammary epithelium but with different severities and phenotypes, consolidated as an in vitro model to study breast cancer biology. As breast cancer is the commonest cause of cancer death in women worldwide, new possibilities of therapies should be researched, suchas the homeopathic Viscum album, a medicine originated from a plant whichextract has cytotoxic effects. In this study, MCF-7, SKBR-3, MDA-MB-321 and PMC-42 cell lines as well as Mesenchymal Stem Cells (MSC)were cultured in the presence of homeopathic Viscum album1x10-400(VA200CH).Cell viability was evaluated by MTT assay and compared between the cell lines. Methods All cell lines were plated in two 96-well plates for 24 hours with culture medium at 37.5 °Cand 5%CO2. After this period, this medium was replaced by anothercontainingVA200CHin concentrations varying from 10 to 100mL/mL. In control group, cells were cultured with medium without VA200CH.These plates were kept in culture for 48 hours. The MTT assay was performed to evaluate the percentage of viable cells, and results were compared to the control group and between tumor cells (MCF-7, SKBR-3, MDA MB-321, PMC-42) and healthy cells (MSC). Results In tumor cells, MTT assay showed that the higher the concentration of VA200CH was,the more able it became to reduce cell viability. Yet, 40mL/mL was the mean concentration enough to cause the death of halfor more of the tumorcells cultured.For MSC, this concentration was calculated as 160mL/mL of VA200CH to achieve the same results. Conclusion This is a promising result that shows the action of VA200CH in several lineage of breast cancer cells and opens up the possibility of using this medicine in the treatment of these tumors, if not alone, at least associated with other medicines or techniques.